Managing investigation, charge sheet & domestic inquiry - Yaacob, Samsudin (Universiti Putra Malaysia Press, 2011)
The objective of this book is to explain proper investigation processes, to form or to design charge sheets and to conduct domestic inquiries. When cases of misconduct or crime arise, an Investigation Officer should take immediate action to determine who is the complainant, victim(s) and witness(es) and if there are any resultant property losses or damages. The purpose of a charge sheet is not just a formality in accusing a person of misconduct. The charge sheet is what specifies the details of alleged misconduct so that it is clear to the person who stands accused. Charges must be specific and the accused must be given the opportunity to be accompanied by his/her committee or union representative to present his/her case.